The Effect of Work Motivation and Work Environment on Employee at PDAM Way Rilau Bandar Lampung City - Rahmawati Rahmawati; M. Oktaviannur (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to analyze the effect of work motivation as well as the work environment on employee performance at PDAM Way Rilau in Bandar Lampung City. Work motivation is measured through internal and external factors that influence employees' desire to achieve organizational goals. Meanwhile, work environment is understood as the physical and psychological conditions of the workplace that can affect employee behavior and productivity. The research method used a survey by distributing questionnaires to employees of PDAM Way Rilau. Data collection was conducted using a cross-sectional approach, as well as data analysis using multiple linear regression methods. The results of this study hope to provide an in-depth understanding of the impact of work motivation as well as the work environment on employee performance in the clean water service sector. The result of this study is the influence between work motivation and work environment for employee performance.